Veikrysset i havet - Eirik Gurandsrud (Heimen)
Abstract The small island municipality in south-western Norway, Kvitsøy, has long maritime traditions. The Norwegian state has operated both a lighthouse and a maritime pilot station on the islands for over 200 years. In the late 1970s the Norwegian Coastal Administration (NCA) suggested closing down the maritime pilot station in Kvitsøy, and running the maritime pilot service from the mainland instead, due to cost benefits. Local politicians started to work strategically towards the government and parliament politicians, in order to get the Norwegian Coastal Administration to invest in a new maritime pilot station in Kvitsøy. The majority of parliament politicians in the early 1980s supported Kvitsøy’s claim, and argued that an investment in a new pilot station would be in line with the Norwegian regional policy to secure settlement and jobs in the outskirts of Norway. The pilot station was finally built in the late 1980s. Later, in 2003, the pilot station was expanded to house also a Vessel Traffic Service-station. The NCA investments in Kvitsøy had little impact on either new settlements, or local jobs. Only two locals were employed at the pilot station, and the other employees lived in on the mainland and did not move to Kvitsøy. The were no locals working on the VTS-station either, other than one in the administration and one cleaning help. The Norwegian regional policy has, since early 1990s, become more fragmented and characterized by local measures. The NCA investments in Kvitsøy had little or no connection with the superior goals of the regional policy, and can therefore be considered as a symbolic political decision. However, the investments have been very important for Kvitsøy in maintaining its maritime traditions.